Mood Disturbances Across the Continuum of Care Based on Self-Report and Clinician Rated Measures in the interRAI Suite of Assessment Instruments - Hirdes, John P.; Morris, John N.; Perlman, Christopher M.; Saari, Margaret; Betini, Gustavo S.; Franco-Martin, Manuel A.; van Hout, Hein; Stewart, Shannon L.; Ferris, Jason (Frontiers in Psychiatry, 2022)
Background: Mood disturbance is a pervasive problem affecting persons of all ages in the general population and the subset of those receiving services from different health care providers. interRAI assessment instruments comprise an integrated health information system providing a common approach to comprehensive assessment of the strengths, preferences and needs of persons with complex needs across the continuum of care. Objective: Our objective was to create a new mood scales for use with the full suite of interRAI assessments including a composite version with both clinician-rated and self-reported items as well as a self-report only version. Methods: We completed a cross-sectional analysis of 511,641 interRAI assessments of Canadian adults aged 18+ in community mental health, home care, community support services, nursing homes, palliative care, acute hospital, and general population surveys to develop, test, and refine new measures of mood disturbance that combined clinician and self-rated items. We examined convergent validity and internal consistency across a diverse care settings and populations. Results: The composite scale combining both clinician and self-report ratings and the self-report only variant showed different distributions across populations and settings with most severe signs of mood disturbance in community mental health settings and lowest severity in the general population prior to the COVID-19 pandemic. The self-report and composite measures were strongly correlated with each other but differed most in population with high rates of missing values for self-report due to cognitive impairment (e.g., nursing homes). Evidence of reliability was strong across care settings, as was convergent validity with respect to depression/mood disorder diagnoses, sleep disturbance, and self-harm indicators. In a general population survey, the correlation of the self-report mood scale with Kessler-10 was 0.73. Conclusions: The Mood Scale variants provide a reliable and valid mental health measure that can be applied across diverse populations and care settings. These scales considers the person’s perspective and clinician views to provide a sensitive and robust measure that takes into account dysphoria, anxiety, and anhedonia.